Christian Trade Unions and European Integration: Organizations and Problems - Barnes, Samuel (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1962)
SummaryChristian trade unions of the countries of « Little Europe » have established organizations to coordinate their European activities and to represent their interests before the agencies concerned with European economic integration. They have been forced to seek allies in order to increase their influence. In this search they have two major alternatives: they can work closely with the International Confederation of Free Trade Unions, or they can try to increase their influence within the Christian Democratic political milieu. This article describes the supranational structure of the International Federation of Christian Trade Unions and analyses the problems of orientation with which its supranational activities has confronted it.The present article was suggested by a broader study of Christian trade unionism in the world. A grant from the Social Science Research Council enabled the author to visit several European countries during the summer of 1959, and this assistance is gratefully acknowledged. Additional research was accomplished in Europe in the summer of 1961.